Jehan de Lanson, Chanson de Geste of the XIII Century : Edited after the Manuscripts of Paris and Bern with Introduction, Notes, Table of Proper Names, and Glossary - Myers, John Vernon (Studies in the Romance languages and literatures, 2018)
Jehan de Lanson is a thirteenth-century French epic poem in alexandrine verse. This edition is based on the manuscripts of Paris and Bern, and includes an introduction, a table of proper names, and a glossary.